The scientificity of community research in Latin America: Critical perceptions of its researchers - Quinteros Flores, Christian; Arcia Hernandez, Pedro (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
This work sought an exploratory approach to the state of community research in Latin America, in relation to its criteria of scientificity and contribution to the knowledge of the territories. The research sought to investigate the epistemological and ontological tendencies of researchers of the "community" in the region who come from different disciplinary backgrounds, which could suggest a certain dispersion in the application of these approaches. The results indicate a strong conviction of the researchers for the capacity of these methodologies to contribute to scientific knowledge and certain divergences regarding the transformative role of these methodologies.